A Radical Approach to Medical Education - A British Perspective - Robson, RH (Journal of Bangladesh College of Physicians and Surgeons, 2011)
DOI: http://dx.doi.org/10.3329/jbcps.v29i2.7948 (J Bangladesh Coll Phys Surg 2011; 29: 58-61)